Nyadran and Paguyuban Budiluhur in Caring for Inter-Religious Harmony - Anif Musyafa’ah Harnianti; Fina Farikhatun Nurul Maqfiroh; Khozinatul Mabruroh; Abdul Najib; Muhammad Syihabuddin Alawy (El Harakah)
This research aims to explore how Nyadran and Paguyuban Budiluhur serve as mediums for maintaining inter-religious harmony in Kapas Village, using Max Weber's social action theory. This qualitative study employs descriptive methods, including observation, semi-structured interviews, and field documentation of the Nyadran tradition and the activities of Paguyuban Budiluhur. The findings indicate that social actions lean towards instrumental rationality, as the Nyadran tradition has been institutionalized in the village's annual agenda, and Paguyuban Budiluhur has become an established foundation. Phenomenological analysis reveals that hybrid social spaces, social interaction, nationalism (driven by motive), and the protection of human rights (in order to motive) are key factors supporting inter-religious harmony in Kapas Village. These factors align with the religious moderation vision of the Indonesian Ministry of Religious Affairs. This paper proposes a recommendation that efforts to maintain religious harmony can be strengthened by creating and institutionalizing social spaces, such as annual traditions or inter-religious organizations. This institutionalization is important, as modern society tends to approach all actions, including social actions, in a rational manner. Rationality can also encourage broader segments of society to participate in efforts to sustain religious harmony and peace.